Small Homeland in the Context (Space) of Civil Identity - V. Kh. Thakahov (Дискурс, 2021)
Introduction. The article analyzes the place, role and functions of the concept of a small homeland in the construction of civil identity. The starting point of the study is the understanding of a small homeland as a set of ideas and practices of the belonging of individuals and groups to the space of the place of birth, origin and primary socialization. A small homeland is what emotionally and practically unites citizens in their loyal affection to the place – physical and symbolic.Methodology and sources. Based on the general concept of the space of places (A. Lefebvre, M. Castells, T. Cresswell, M. Auger); P. Shtompka's theory of cultural trauma and A.O. Boronoev's ideas of structural schematization of a small homeland, it is originally presented a sociological analysis of the problem of the loss of a small homeland as a result of forced relocations (the case of flooded areas). As relevant sources the author use the documents and memoirs on the phenomenon of the loss of a small homeland; also on memories of eyewitnesses, and on artistic reflection of farewell to the place of birth. The purpose of the study is to identify the role of the loss of a small homeland in the functioning and reproduction of the civic identity of the place.Results and discussion. As a result of the study it has been shown that the loss of a small homeland determines: a) the rupture of social and cultural ties; b) the emergence of grassroots self-organization of Mologzhan activists who are re-constructing civic urban identity; c) production of commemorative practices of a regular type (cases of Mologa and Circassian auls); d) active formation of cultural discourse in which the small homeland of the place is positioned as a subjective value and one of the foundations of the life world.Conclusion. A small homeland as a representation and social practice in the space of civic identity ensures through its agents the reproduction of social interaction (real or imaginary) with a place and the maintenance of socio-cultural ties with it within the natural and cultural landscape of communities. It also promotes recognition, confirmation of the identity of the place. The loss of a small homeland (physical and symbolic) gives rise to various social practices of memory, rebirth and oblivion.